2007
DOI: 10.1037/0021-843x.116.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and serotonergic vulnerability to depression: Convergent findings.

Abstract: Cognitive reactivity (CR) is a psychological vulnerability marker of depression, whereas response to acute tryptophan depletion (ATD; a serotonergic challenge procedure) is a biological vulnerability marker. The aim of this study was to investigate the relationship between these markers. Thirty-nine remitted depressed patients participated in 2 ATD sessions in a double-blind crossover design. CR, assessed prior to the ATD sessions, predicted depressive response to high-dose ATD. CR also diminished the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 81 publications
3
31
0
1
Order By: Relevance
“…Taken together, these findings are also in line with the previously mentioned study showing a decreased attentional control for negative stimuli after rTMS of the DLPFC ). Interestingly, tryptophan depletion causes a temporary increase in depressive symptoms among formerly depressed persons (e.g., Booij & Van der Does, 2007; but see Leyton et al, 1997). This effect is not observed in people who show no history of depressive episodes or other risk factors (Ruhé, Mason, & Schene, 2007).…”
Section: Summary: An Integrative Frameworkmentioning
confidence: 98%
“…Taken together, these findings are also in line with the previously mentioned study showing a decreased attentional control for negative stimuli after rTMS of the DLPFC ). Interestingly, tryptophan depletion causes a temporary increase in depressive symptoms among formerly depressed persons (e.g., Booij & Van der Does, 2007; but see Leyton et al, 1997). This effect is not observed in people who show no history of depressive episodes or other risk factors (Ruhé, Mason, & Schene, 2007).…”
Section: Summary: An Integrative Frameworkmentioning
confidence: 98%
“…LEIDS-r scores have been found to predict depression incidence in multiple longitudinal studies and to correlate with depression risk factors, such as depression history (Moulds et al, 2008), genetic markers of depression (Antypa & van der Does, 2010), and reaction to tryptophan depletion (Booij & van der Does, 2007). Following Steenbergen et al (2015), before responding to the items, participants were requested to take a few minutes to imagine how they would feel and think if they were to experience a sad mood and then to specify, on a 5-point Likert scale ranging from 0 (i.e., 'not at all') to 4 ('very strongly'), the extent to which each statement applied to them.…”
Section: Leids-rmentioning
confidence: 99%
“…First, the reinstatement of negative thinking patterns is a conceptual analog to the (cognitive) theory of depression, which precisely states that a depressive episode is triggered when a mild sad mood state reactivates negative thinking in vulnerable individuals. Second, CR is associated with biological markers of depression vulnerability (Booij & van der Does, 2007) and genes that are implicated in the pathophysiology of depression (Antypa & van der Does, 2010). Third, Raes et al (2009) found that an evidence-based treatment to reduce depression relapse also reduced selfreported CR in a mixed sample including recovered depressed individuals and non-clinically depressed individuals (compared to a matched control group).…”
Section: Application To the Fear-conditioning Model Of Anxietymentioning
confidence: 99%